Appendix 3.2: Popularizing Political Rehabilitation: Bongbong Marcos’s Friendster - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
The Bangui windmills in Ilocos Norte were prominently featured in Bongbong Marcos’s 2010 campaign materials. This screenshot of his profile in the defunct social media platform Friendster features an infantilized cartoon of Marcos holding a pinwheel, images of windmills behind a photograph of himself with his wife and children, and a link to an internet browser game called “Windmill City.” The profile page also stated that Marcos had been a member of Friendster since 2004, which shows how early Marcos adopted the use of online social networking platforms for his political rehabilitation. That was to be his last term as governor of Ilocos Norte, 2004–2007.